Early Recurrence of a Cardiac Malignant Fibrous Histiocytoma - López, Laura R.; Bauza, Ángela G.; Cereijo, Jose M. M.; Álvarez, José R.; Názar, Belén A.; Quiroga, Juan S. (Scientific Research, 2013)
Malignant fibrous histiocytoma (MFH) is a rare tumor of the heart and the patients with these tumors usually have a poor prognosis. We report a case of MFH with an origin from the left superior pulmonary vein, involving the left atrium and protruding through the mitral valve, which needed urgent surgery. Complete resection was performed but local recurrence was detected one month later.
Keywords: Malignant Fibrous Histiocytoma; Early Recurrence